Solid Oxide Fuel Cell Components Interfacial Compatibility of SOFC Glass Seals - Kaur, Gurbinder (Springer International Publishing : Imprint: Springer, 2016)
The only resource to focus on solving the challenges of glass seals in SOFCs Provides insight into interaction mechanisms at all the various interfaces within the fuel cell Analyzes basic concepts systematically and clearly, thoroughly explaining more complex topics through plentiful illustrations and diagrams This book examines the various interfacial reactions that take place when  glass seals come into contact with components of SOFCs in reducing and oxidizing conditions.  In developing an understanding of the structure and function of SOFCs, interfacial compatibility is an imperative criterion. This book addresses the technical challenges of developing sealants to avoid leakage losses at high operating temperatures, which are profoundly impactful to the efficiency of the fuel cell. This resource is important for anyone working with or studying fuel cell design and development, and is a pivotal source of cutting-edge information for research groups actively engaged in developing hermetic and stable seals which show minimum interfacial chemical reaction with interconnect and electrolyte.